Interpol’s Role in Combating Transnational Cybercrime in Southeast Asia: A Case Study of Operations HAECHI I–VI - Ainin Zikra (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of Interpol in combating transnational cybercrime in Southeast Asia through Operations HAECHI I to VI. Employing a qualitative non empirical research design and an explanatory case study approach, the research analyzes how Interpol facilitates international cooperation against cyber enabled financial crime across multiple jurisdictions. Data were derived from official Interpol operational reports, annual publications of the Interpol Financial Crime and Anti Corruption Centre, documents issued by the ASEAN Secretariat, reports from international organizations, and relevant scholarly literature. Qualitative content analysis and process tracing were used to identify institutional mechanisms and assess operational outcomes. The findings indicate that cyber enabled financial crime has evolved into a multidimensional threat affecting economic stability, governance capacity, and individual security throughout the region. Interpol has strengthened regional responses by institutionalizing intelligence exchange, coordinating cross border investigations, and supporting asset recovery through mechanisms such as the Interpol Financial Crime and Anti Corruption Centre and the Anti Money Laundering Rapid Response Protocol. Although HAECHI operations have generated substantial enforcement outcomes, persistent challenges remain in legal harmonization, regulatory capacity, and cryptocurrency related investigations. The study concludes that Interpol functions as a critical governance actor whose effectiveness depends on sustained institutional adaptation and deeper regional cooperation.